Failure investigation of the pulverizing fan of ventilation mill. (March 2015) - Yao, Zongwei; Wang, Guoqiang; Song, Lianguo; Ma, Yu; Li, Xuefei
Highlights: Failure analysis of cracks occurred in pulverizing fan of ventilation mills. Nonlinear stress/strain analysis of the whole assembled pulverizing fan. Comprehensive experiments revealed the nature of the failure. Abstract: Long-term continuous high-speed rotation provides the conditions for the occurrence of various failures of ventilation mill (VM) parts, such as the pulverizing fan. Pulverizing fan failure leads to dynamic unbalance of the rotating mechanism, which causes significant damage to the whole system, serious casualties, and high financial loss that may exceed the direct material damage considerably. This study aimed at diagnosing the cause of pulverizing fan damage. To identify the reasons behind pulverizing fan failures, stress state simulations and experimental investigations were performed. Experiments comprised visual and metallographic examinations, chemical composition analyses, mechanical property tests, and strength test, which revealed the nature of the failure. Numerical–experimental analysis results indicate that pulverizing fan failures are mainly caused by inappropriate structural designs and harsh operating conditions. Results also emphasize the importance of comprehensive quality control of VM pulverizing fan.